(3JMaI GdWdGH aj GdYed HQHY GdGSWQdGHs - (3Ydj Hf YKeGf Hf eMeO Hf CMeO, CHh GdHbGA GdYPQj, hjYQa H (B: (3GHf GdbGUM,J (B801 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI aEfi deG QCjJ CcKQ GdfGS bO CgedG GdGTJYGd HYde ChbGJ GdUdhGJ hbdOhG s
(3BNQgG (B:s
(3GdaQSN KdGKI CejGd hGdejd CQHYI CdGa PQGY bGd GdefUa hdjcf gPG BNQ GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B5 - (3U (B727s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B165 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B18 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B26) s
Keywords: (3Gdadcs